A new species of Heimioporus (Boletaceae) from southern China - Chen, Xiang-Nyu; Zhang, Ming; Li, Tai-Hui; Zeng, Nian-Kai (Phytotaxa, 2019)
Heimioporus sinensis, collected from tropical and subtropical areas of China, is introduced as a new species based on both morphological characters and molecular data. The species is characterized by the purplish red to deep magenta pileus, the reticulated stipe, the irregularly reticulate to reticulate-alveolate basidiospores 11.5–13.5 × 8–9.5 μm, and a trichodermal to intricately trichodermal pileipellis. Phylogenetic analyses based on the nuc 28S rDNA D1-D2 domains (28S) and the translation elongation factor 1-α gene (tef1-α) showed that H. sinensis is a distinct member of the genus Heimioporus in the subfamily Xerocomoideae.